PENERAPAN PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK (PMR) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 015 SEREMBAN JAYA KECAMATAN RIMBA MELINTANG - Sopia Julita; Hendri Marhadi; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The design of the research is classroom action research,aims to improve the learning out comes of fourth SDN 015 Seremban Jaya, with research subjects 12 boys an 8 girls. Implementation of this research took place on 19 March 2015 to 27 March 2015. The data collected in this study is the techer activity sheet, sheet student activity and learning. In this study obtained a score of basic or learning outcomes before action 55,25, after the action on the UH I has increased by 15,75%, with an average of 71,00 and at UH II also an increase of 5,50, with an average 76,50. Teachers each cycle activity also increased first cycle of the first meeting and the meeting second 61,53% 65,38% an increase of 3,85%, whereas at the meeting of the first cycle second 78,84% means an increase of 13,46% and meeting second of the cycle second 86,53% increase of 7,69%. Students activity also increased each cycle of the first meeting and the meeting second 59,61% 67,30% an increase of 7,69%, while the first meeting of the second cycle 71,15% with an increase of 3,85% and e meeting second cycle second 82,69% with an increase of 11,54%. From the discussion above it can be concluded that the application of the approach Realistic Mathematics education can improve mathematics learning outcomes fourth grade student of SDN 015 Seremban Jaya subdistrict Rimba Melintang.Keyword : Learning approach Realistic Mathematics, Mathematics Learning outcomes2